ANT SPECIES DIVERSITY STUDY USING PITFALL TRAPS IN A SMALL YARD IN BOGOR BOTANIC GARDEN, WEST JAVA, INDONESIA - Henny Herwina; Koji Nakamura (BRIN Publishing (Penerbit BRIN), 2007)
The ant fauna in a small yard in Bogor Botanic Garden, West Java,Indonesia was investigated using pitfall traps. Regular sampling was carriedout weekly or biweekly for 3.5 years from March, 2000 to November, 2003.The accumulation curve for the species number collected was asymptotic,indicating the completeness of the sampling. A total of 29424 individuals,represented by 55 species in 27 genera, 17 tribes and 6 subfamilies werecollected. Myrmicinae was the most abundant with 19 species (34.6 %) and19524 individuals (66.4 %), followed by Formicinae with 15 species (27.3 %)and 4470 individuals (15.2 %), and Ponerinae with 12 species (21.8 %) and2880 individuals (9.8 %). Aenictinae, Dolichoderinae and Cerapachinae had 4(7.3 %), 4 (7.3 %) and 1 (1.8 %) species, and 1716 (5.8 %), 832 (5.8 %) and 2(0.01 %) individuals, respectively. The present results were compared with Itoet al. (2001), who collected ant species in Bogor Botanic Garden using 7methods, including pitfall traps.